2015
DOI: 10.1002/tox.22159
|View full text |Cite
|
Sign up to set email alerts
|

Review: Morphofunctional and biochemical markers of stress in sea urchin life stages exposed to engineered nanoparticles

Abstract: We describe the use of different life stages of the Mediterranean sea urchin Paracentrotus lividus for the assessment of the possible risk posed by nanoparticles (NPs) in the coastal water. A first screening for the presence of NPs in sea water may be obtained by checking their presence inside tissues of organisms taken from the wild. The ability of NPs to pass from gut to the coelomic fluid is demonstrated by accumulation in sea urchin coelomocytes; the toxicity on sperms can be measured by embryotoxicity mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 60 publications
1
27
0
2
Order By: Relevance
“…Exposure of P. lividus and Arbacia lixula sea urchins to heavy rare earth elements affected embryogenesis, fertilization, cytogenetic, and redox endpoints (Oral et al 2017). Other studies focused on the fate, behavior, and effects of nanomaterials (NMs) in the marine environment, showing their toxicity for sea urchin embryos at different larval stages (Fairbairn et al 2011;Burić et al 2015;Gambardella et al 2016;Kanold et al 2016;Torres-Duarte et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of P. lividus and Arbacia lixula sea urchins to heavy rare earth elements affected embryogenesis, fertilization, cytogenetic, and redox endpoints (Oral et al 2017). Other studies focused on the fate, behavior, and effects of nanomaterials (NMs) in the marine environment, showing their toxicity for sea urchin embryos at different larval stages (Fairbairn et al 2011;Burić et al 2015;Gambardella et al 2016;Kanold et al 2016;Torres-Duarte et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Reports describing the toxic effects of chemicals, pharmaceuticals, insecticides, pesticides, and other environmental contaminants on sea urchin embryos and adults have been recently published [112,[139][140][141][142][143]. Investigators in marine research have paid particular attention to the fast growth of submicroscopic materials contaminating marine and coastal ecosystems and have analyzed biochemical and histochemical markers of toxicity, taking advantage of the sensitivity of sea urchin gametes, embryos, and adult cells [144]. Recently, researchers have developed new computation methods and a new toxicity index, integrating the frequency of abnormal embryos obtained after treatment with marine waters and sediments with the adverse effects observed during development.…”
Section: Sea Urchin Cells and Embryos Respond To External Agents: Hummentioning
confidence: 99%
“…The reproductive, developmental, and embryotoxicity of NPs represent a particular area of interest to scientists in the area of nanotoxicology [ 23 , 24 , 25 , 26 ]. Prior studies have shown that echinoderms, and especially sea urchins, represent one of the most suitable models in the assessment of reproductive, developmental, and embryotic toxicity of NPs in the aquatic environment [ 27 , 28 , 29 ]. Sea urchins have been described as a key species of marine benthic communities attached to hard bottoms, with habitats ranging from a few centimeters deep to 20 or more meters [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sea urchins have been described as a key species of marine benthic communities attached to hard bottoms, with habitats ranging from a few centimeters deep to 20 or more meters [ 30 ]. Sea urchin, and general echinoderm, fertilization takes place outside the maternal body [ 27 ]. Embryos and larvae of sea urchins can swim in the water column and represent good food for other organisms [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation